2021
DOI: 10.3390/genes12091360
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity and Autism Spectrum Disorders as the Core Symptoms of AUTS2 Syndrome: Description of Five New Patients and Update of the Frequency of Manifestations and Genotype-Phenotype Correlation

Abstract: Haploinsufficiency of AUTS2 has been associated with a syndromic form of neurodevelopmental delay characterized by intellectual disability, autistic features, and microcephaly, also known as AUTS2 syndrome. While the phenotype associated with large deletions and duplications of AUTS2 is well established, clinical features of patients harboring AUTS2 sequence variants have not been extensively described. In this study, we describe the phenotype of five new patients with AUTS2 pathogenic variants, three of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…After the initial description by Beunders et al, a meta-analysis using the data of 31 patients with AUTS2 syndrome obtained from seven studies, in addition to five newly identified clinical cases, supported that the patients with ADHD and/or ASDs, who carry mutations at 3′ end of the AUTS2 locus showed higher ASSS values compared with individuals with AUTS2 aberrations at the 5′ end of the locus [ 35 ]. These findings imply that the ablation of C-terminal region of AUTS2 may contribute to the onset of AUTS2 syndrome.…”
Section: Genotype–phenotype Correlations Of Auts2 Syndromementioning
confidence: 99%
“…After the initial description by Beunders et al, a meta-analysis using the data of 31 patients with AUTS2 syndrome obtained from seven studies, in addition to five newly identified clinical cases, supported that the patients with ADHD and/or ASDs, who carry mutations at 3′ end of the AUTS2 locus showed higher ASSS values compared with individuals with AUTS2 aberrations at the 5′ end of the locus [ 35 ]. These findings imply that the ablation of C-terminal region of AUTS2 may contribute to the onset of AUTS2 syndrome.…”
Section: Genotype–phenotype Correlations Of Auts2 Syndromementioning
confidence: 99%
“…Depending on the location of AUTS2 point mutations/deletions the phenotype ranges from an isolated neurodevelopmental disorder (e.g., autism spectrum disorder, attention deficit hyperactivity disorder, learning disabilities and/or intellectual disability) to a syndromic disorder with microcephaly, short stature, feeding difficulties, heart defects, skeletal anomalies, contractures and dysmorphic features (Beunders et al, 2013;Beunders et al, 2016;Saeki et al, 2019;Sanchez-Jimeno et al,…”
mentioning
confidence: 99%
“…The data for AUTS2 syndrome were adapted from Sanchez-Jimeno et al which is based on nine different studies (Sultana et al, 2002;Kalscheuer et al, 2007;Bakkaloglu et al, 2008;Huang et al, 2010;Girirajan et al, 2011;Jolley et al, 2013;Nagamani et al, 2013;Liu et al, 2015;Beunders et al, 2016). In addition, the data include a cohort of five patients published by Sanchez-Jimeno et al (Sanchez-Jimeno et al, 2021). The data for the FBRSL1 syndromic phenotype is based on the three patients published in Ufartes et al (Ufartes et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations